2019
DOI: 10.22201/fca.24488410e.2020.2215
|View full text |Cite
|
Sign up to set email alerts
|

In emerging economies, the effect of excessive credit growth and non - performing loans on banking crisis

Abstract: Crediting in the banking sector plays an important role in developed and developing countries, which have built their financial system more on banking rather than capital markets. For this reason, it is monitored continuously by public authorities and measures are taken to control credit supply in rapid credit increases. In addition, strict provisioning rules for non-performing credits are under practice for non-performing loans. It is well known that in emerging markets strong credit growth in a given period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…According to previous studies around that time, such as that conducted by Corsetti, Pesenti and Roubini (1999), the sharp currency depreciation and investors' panic were reasons for the crises, as demonstrated in Model 3 and Model 4 for emerging economies. Our results are consistent with a recent study by Tunay et al (2020) which argues that banking crises in emerging economies are likely caused by systemic risk with high credit default. Thus, the effect of house price coupled with household debt is more pronounced in advanced economies.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…According to previous studies around that time, such as that conducted by Corsetti, Pesenti and Roubini (1999), the sharp currency depreciation and investors' panic were reasons for the crises, as demonstrated in Model 3 and Model 4 for emerging economies. Our results are consistent with a recent study by Tunay et al (2020) which argues that banking crises in emerging economies are likely caused by systemic risk with high credit default. Thus, the effect of house price coupled with household debt is more pronounced in advanced economies.…”
Section: Resultssupporting
confidence: 93%
“…In their study of an emerging country, Garber et al (2019) proved that the tremendous increase in household debt preceded Brazil's economic recession. Nevertheless, in a more recent study of 23 emerging economies, Tunay et al (2020) found opposite evidence showing that crises in the banking sector were headed by the current account deficit and systemic risk as consequence from credit default which explained the twin crisis hypothesis.…”
Section: The Role Of Household Debt and House Price In Banking Crisesmentioning
confidence: 92%
“…Antunes et al [6] proposed the use of fuzzy support vector machine (FSVM) algorithm to improve traditional SVM and obtained correct results. Tunay et al [7] constructed a Partial Least-Squares Logistic model and conducted an empirical study on ST listed companies in stock markets. Misman and Bhatti [8] used multivariate discriminant analysis, Logistic regression, and neural network methods to establish a combined classifier model.…”
Section: Related Workmentioning
confidence: 99%
“…In relation to Non Performing Loans, there are several studies that discuss Non Performing Loans. Research [8] shows that banks with large total assets tend to affect the level of Non Performing Loans (NPL), he variable size of the bank is not widely studied for Non Performing Loans (NPL) in Indonesia [9]. Then according to [10] evaluated the effectiveness of the use of instruments in reducing systemic risk in 49 countries and some instruments (LTV and GWM) were effective in reducing procyclicality but their effectiveness was highly dependent on shocks in the financial sector.…”
Section: Empirical Studiesmentioning
confidence: 99%